2018
DOI: 10.1093/neuonc/noy027
|View full text |Cite
|
Sign up to set email alerts
|

The clinical trials landscape for glioblastoma: is it adequate to develop new treatments?

Abstract: The clinical trials landscape for GBM is characterized by long development times, inadequate dissemination of information, suboptimal go/no-go decision making, and low patient participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 32 publications
1
97
0
Order By: Relevance
“…At recurrence, a range of treatment options are available and include additional debulking surgery, if possible, with administration of chemotherapies such as nitrosoureas with/without antiangiogenic therapy using bevacizumab. These additional treatment strategies have not been standardized, and results in randomized clinical trials have failed to show a significant survival benefit, leading many patients to participate in clinical trials of investigational therapies (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…At recurrence, a range of treatment options are available and include additional debulking surgery, if possible, with administration of chemotherapies such as nitrosoureas with/without antiangiogenic therapy using bevacizumab. These additional treatment strategies have not been standardized, and results in randomized clinical trials have failed to show a significant survival benefit, leading many patients to participate in clinical trials of investigational therapies (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Even with intensive treatments, GBM virtually always recurs. Existing chemotherapies have been shown to be only modestly effective as they extend median survival by a few months [2] and clinical trials of new therapeutic agents have failed to show any improvements in survival [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research of clinical trials of all glioblastomas registered between 2005 and 2016 showed that, among the 417 confirmed clinical trials, 93% of clinical trials were in phases I or II, and 26% of all clinical trial patients participated in the phase III study. Of the eight completed phase III trials, only one reported positive results (28). Among patients with high-grade gliomas, there are long development times, insufficiently disseminated information, poor decision-making regarding traveling, and low patient participation (28).…”
Section: Discussionmentioning
confidence: 99%
“…Of the eight completed phase III trials, only one reported positive results (28). Among patients with high-grade gliomas, there are long development times, insufficiently disseminated information, poor decision-making regarding traveling, and low patient participation (28). Bloodbrain barrier penetration, redundancy of intracellular signaling pathways, tumor molecular heterogeneity, and lack of validated biomarkers have been fully concerned and thought to be the main obstacles in glioma research (29,30).…”
Section: Discussionmentioning
confidence: 99%